Cardiovascular risk factors in women with inheritable thrombophilia a decade after single or recurrent hypertensive disorder of pregnancy. (1st October 2016) - Abheiden, Carolien N. H.; Thijs, Abel; de Vries, Johanna I. P.; de Boer, Marjon A.
ABSTRACT: Objective : To described cardiovascular risk factors in women with inheritable thrombophilia 8–19 years after early-onset hypertensive disorders of pregnancy (HD) with or without recurrent HD. Methods : Women with recurrent HD were compared with women with single HD, for physical examination and cardiovascular parameters in serum. Results : Systolic blood pressure, diastolic blood pressure, and albumin: creatinine ratio were higher in women with recurrent HD compared with women with single HD ( p = 0.046, p = 0.029, and p = 0.008, respectively). In both groups 72.7% had an increased cardiovascular risk. Conclusion : Women with inheritable thrombophilia after single or recurrent HD have a high cardiovascular risk.